Medycyna kartezjańska – jej cele i uwarunkowania - Stegliński, Tomasz (Humaniora. Czasopismo Internetowe, 2019)
The article deals with the less popular part of Descartes’ philosophy, namely his medicine. Outlined, it has not reached its mature form. Its basic examples are above all the anatomical works of the philosopher: “Man,” “Description of the Human Body” and in a sense the text of “Passion of the Soul”; in addition, several statements from “Dissertation on the Method” or “Metaphysical Meditations,” finally some youthful letters . In the following text I try to link various threads in this area to answer some basic questions: what was Cartesian medicine supposed to be? What was its foundation? What beliefs and hopes did the author associate with this part of science? How did he want to build medicine on the solid grounds of his metaphysics? I divide the text of the article into two parts. In the first part I deal with the objectives medicine was to serve. I present its role in consolidating the view of the material nature of life and its impact on thinking in man. I present five main purposes of medical science, such as: self-knowledge; a pain relief technique; a way to extend life; neutralization of corporality as a state of mind; finally the existance of medicine as the basis for ethics. In the second part I talk about the methodological conditions of Descartes’s rationalism. I show how it was possible to fund knowledge on the practical application of medical techniques. I try to show the effect of this perspective.